Hatching Failure and Success of Hawksbill Sea Turtles (Eretmochelys imbricata) in Semi-Natural Nests Karimunjawa. - Rahayu, Sari Sistyawati; Suryanti, Suryanti; Ayuningrum, Diah; Lundin, Kennet (Biosaintifika: Journal of Biology & Biology Education, 2023)
Hatching success and failure is influences by the interaction between biotic and abiotic factors during the incubation period. Non optimal nest is susceptible to bacterial contaminated eggs during incubation period and hatchling morphology. The purpose of the study is to understand the relationship between environmental conditions of semi natural nest with bacteria contaminant, hatchlings allometry and abnormality. The method used was quantitative descriptive which are nest temperature and humidity measurement, hatchlings allometry measurement, bacteria observation of gram negative with EMB (Eosin Methylene Blue) agar, TPC (Total Plate Count), bacteria characteristic morphology and hatchlings abnormality observation. The result showed that semi natural nest have high temperature (30˚C) and high humidity (70%) caused smaller hatchlings and negative allometry growth, hatchlings abnormality and bacterial contaminant. TPC showed that the number of bacteria unhatched eggs (1,42 x ) more than hatched eggs (1,03 x ). The bacteria colonies were suspected to be from Enterobacteriaceae family according to microscopic and macroscopic morphological characteristic. Macroscopically, the bacteria morphology is dominated by a round shape, concentric surface, flat edges, flat elevation and pink color, meanwhile microscopic form is bacilli. There is significant correlation between environmental conditions of semi natural nest with hatchlings growth, hatchlings abnormality and eggshells bacteria